Rain attenuation in broadband satellite service and worst month analysis - Idrissa Abubakar; Jafri Bin Din; Lam Hong Yin; Manhal Alhilali (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Satellite link design, link margin and services at lower bands of satellite spectrum has been facing the challenges of meeting the demands for higher bandwidth requirements. Satellite operators and service providers are been compelled to migrate to the use of higher frequencies above 10 GHz. These higher frequencies were discovered to be vulnerable to atmospheric degradation creating the challenge of service availability especially for tropical rain zones with higher rainfall intensities and longer rain event durations. This study strive to evaluate the profile of rainfall and the monthly and annual variability to improve the design parameters of satellite propagation. Two yeas rainfall measurement campaign was conducted in Abuja at Nigcomsat-1R ground station with a view to understanding the characteristics of Abuja rain. The location of the site is on lat. 9.06o N and lon. 7.48o E. Tipping bucket rain gauge was used for point rain rate and 1.8 m VSAT antenna was installed to monitor the rain induced attenuation on satellite broadband signal. The results shows a huge variability between month to month as well as annual average between 2016 and 2017. The performance of broadband satellite service was found to largely to depend on the quality of the carrier power above the system noise rather than bandwidth capacity or the receive signal level while higher attenuations are associated with higher rain intensities and the slant path effects.